Evaluation of non-continuous temperature-monitoring practices for vaccine storage units: a Monte Carlo simulation study. - Leidner, Andrew J.; Lee, Carla E.; Tippins, Ashley; Messonnier, Mark L.; Stevenson, John M. (Journal of Public Health: From Theory to Practice (2198-1833), 2021)
Objectives: Evaluate different non-continuous temperature-monitoring practices for detection of out-of-range temperatures (above or below the recommended temperature range of 2–8 °C for refrigeration units), which are called excursions, within vaccine storage units. Methods: Simulations based on temperature data collected by 243 digital data loggers operated in vaccine storage units at health-care providers who participated in a CDC-sponsored continuous temperature monitoring pilot project, from 2012 to 2015. In the primary analysis, we evaluate: (1) twice-daily current temperature readings without minimum and maximum readings (min/max), (2) twice-daily current temperature readings with once-daily min/max, and (3) twice-daily current temperature readings with twice-daily min/max. Results: Recording current temperature twice daily without min/max resulted in the detection of 4.8—6.4% of the total number of temperature excursions. When min/max readings were introduced, the percentage of detected temperature excursions increased to 27.8—96.6% with once-daily min/max and to 34.8—96.7% with twice-daily min/max. Conclusions: Including min/max readings improves the ability of a temperature monitoring practice to detect temperature excursions. No combination of the non-continuous temperature monitoring practices were able to consistently detect all simulated temperature excursions.